Correction: Methyl Farnesoate Plays a Dual Role in Regulating Drosophila Metamorphosis. - Wen, D.; Rivera-Perez, C.; Abdou, M.; Jia, Q.; He, Q.; Liu, X.; Zyaan, O.; Xu, J.; Bendena, W.G.; Tobe, S.S.; Noriega, F.G.; Palli, S.R.; et al. (PLoS Genetics, 2017)
[This corrects the article DOI: 10.1371/journal.pgen.1005038.].